Urbanization and women’s body weight: Evidence from Nigeria - Abay, Kibrom A.; Amare, Mulubrhan (International Food Policy Research Institute, 2018)
The prevalence of overweight and obesity are increasing in many African countries and hence becoming regional public health challenges. We employ satellite-based night light intensity data as a proxy for urbanization to investigate the relationship between urbanization and women’s body weight. We use two rounds of the Demographic and Health Survey data from Nigeria. We employ both nonparametric and parametric estimation approaches that exploit both the cross-sectional and longitudinal variations in night light intensities.